2017
DOI: 10.1080/17445647.2017.1379913
|View full text |Cite
|
Sign up to set email alerts
|

Generic identification and classification of morphostructures in the Noachis-Sabaea region, southern highlands of Mars

Abstract: The Noachis-Sabaea region in the southern highlands preserves some of the oldest Martian crust. It records deformation by both endogenic and exogenic processes. This deformation includes giant impacts and their impact stresses, which could have resulted in both the reactivation and modification of pre-impact tectonic structures, in addition to impactgenerated tectonic structures. There are also widespread extensional and compressional tectonic structures, which were formed due to endogenic processes. We have p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Deep basins are, in particular, the most appropriate candidates to investigate the geological history because, due to eolian erosion, the sedimentary record in shallower basins is often undetectable. Furthermore, in the case of a one‐plate planet such as Mars (Banerdt et al, ; Breuer & Spohn, ), impact craters are among the few natural phenomena that are able to deform the surface (Ruj et al, ) and act as sedimentary basins with considerable and well‐developed steep slopes (see Table for crater walls' slopes). Erosional processes occurred on the basin walls creating sediments that accumulated within the basin, which acted as a terminal sink.…”
Section: Resultsmentioning
confidence: 99%
“…Deep basins are, in particular, the most appropriate candidates to investigate the geological history because, due to eolian erosion, the sedimentary record in shallower basins is often undetectable. Furthermore, in the case of a one‐plate planet such as Mars (Banerdt et al, ; Breuer & Spohn, ), impact craters are among the few natural phenomena that are able to deform the surface (Ruj et al, ) and act as sedimentary basins with considerable and well‐developed steep slopes (see Table for crater walls' slopes). Erosional processes occurred on the basin walls creating sediments that accumulated within the basin, which acted as a terminal sink.…”
Section: Resultsmentioning
confidence: 99%
“…Our favored idea is that the position of the ELD Mound is the product of the intersection of a radial fracture system (related to the interior crater impact event) and the presence of a pre‐existing regional fault and its damaged zone (Caine et al., 1996; Ruj et al., 2017), which creates the required permeability.…”
Section: Discussionmentioning
confidence: 99%
“…Our favored idea is that the position of the ELD Mound is the product of the intersection of a radial fracture system (related to the interior crater impact event) and the presence of a pre-existing regional fault and its damaged zone (Caine et al, 1996;Ruj et al, 2017), which creates the required permeability. After a detailed work on the presence of hydrated minerals in Becquerel, Koeppel et al (2022) concluded on the basis of numerical modeling of THEMIS images of ELDs (referred to in the article as SBLDs) that the contribution of water (if any) was minimal.…”
Section: Proposed Processmentioning
confidence: 99%
“…Previous studies provide global and regional maps of Sinus Sabaeus (Figure 2). Two geologic maps with a scale of 1:5,000,000 had covered the area before: Moore (1980) and Ruj et al (2017), the latter having a more morphostructural focus. Our study area has been included in two global geologic maps of Mars: Greeley and Guest (1987), with a scale of 1:15,000,000, and Tanaka et al (2014), with a scale of 1:20,000,000.…”
Section: Introductionmentioning
confidence: 99%
“…A) The Geologic map of the Sinus Sabaeus Quadrangle of Mars(Moore, 1980), that defines 8 units in our area of interest: 'material of youngest craters' (c5),' material of young craters' (c4), 'material of intermediate age craters' (c3), 'material of old craters' (c2), 'material of oldest craters' (c1), 'cratered plains material' (pc), 'plains material' (p), 'hilly, channeled and cratered material' (hcc); and 3 structures: 'crater rim crests', 'buried crater rim crests', and 'small channels'. B) The Generic identification and classification of morphostructures in the Noachis-Sabaea region, southern highlands of Mars(Ruj et al, 2017), which includes 3 different units: 'early Noachian highlands' (eNh), 'middle Noachian highlands' (mNh) and 'early Hesperian highland unit' (eHh); and some structures: 4 types of impact craters according to their degradation state, going from 'type 3' (the youngest) to 'ghost crater' (the oldest), 'normal faults', 'wrinkle ridges' and 'lobate scarps'. C) The Geologic map of the eastern equatorial region of Mars(Greeley & Guest, 1987), with 3 structures: 'crater rim and ejecta material' (c), 'smooth floor material' (s) and 'wrinkle ridges' (Hr); and 4 units: 'mottled smooth plains' (Hplm), 'ridged' (Nplr), 'etched' (Nple), and 'dissected' (Npld).…”
mentioning
confidence: 99%